2020
DOI: 10.1051/bioconf/20202700086
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological safety assessment of ZeolFat energy feed additive

Abstract: Development of inexpensive and environmentally friendly feed additives based on waste from the food industry and expired products as energy sources for animals is of current relevance and high demand. The study aimed to test the toxicological safety of ZeolFat energy feed additive (EFA) on laboratory animals. The tests on white rats showed that ZeolFat EFA is a low-toxic feed product with no cumulative properties revealed. The animals exhibited satisfactory physical state and a good appetite during experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Feed additives are nonnutritive products added to the basic feed mix to enhance productive function and growth, preserve feeds, increase the efficiency of feed utilization, or benefit metabolism and animal health [ 1 , 2 ]. Numerous studies and individual experiences gained by livestock owners have shown that the comprehensive feeding of animals, especially for high-yielding cattle, is impossible without highly effective feed additives such as antibiotics [ 3 , 4 ]. The beneficial effect of antibiotics as a growth stimulant was discovered in the 1940s [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Feed additives are nonnutritive products added to the basic feed mix to enhance productive function and growth, preserve feeds, increase the efficiency of feed utilization, or benefit metabolism and animal health [ 1 , 2 ]. Numerous studies and individual experiences gained by livestock owners have shown that the comprehensive feeding of animals, especially for high-yielding cattle, is impossible without highly effective feed additives such as antibiotics [ 3 , 4 ]. The beneficial effect of antibiotics as a growth stimulant was discovered in the 1940s [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%